KINERJA KADER PARTAI KEADILAN SEJAHTERA (PKS) TINGKAT DEWAN PERWAKILAN CABANG (DPC) RUMBAI PADA PEMILIHAN UMUM LEGISLATIF 2014 - Perdana, Muhammad Adrian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study examines the performance of the organization which in thiscase is the performance of the DPC PKS cadres Tassel winning smoothparliamentary elections in 2014 dapil Rumbai. PKS increased the vote in eachperiod of the elections at both national and regional levels, particularly duringthe parliamentary elections in the Riau region experienced two periods reinforcethe recent elections. It is certainly not out of the performance of cadres whosuccessfully captured the public sympathy meilih for Islamic political ideology.The method used in this research is descriptive research with qualitative analysis.Qualitative research is an approach that uses a specific social situation with adescription of the true reality, formed by words based on the techniques ofcollecting and analyzing relevant data and obtained from the scientific situation.Qualitative research is to describe the characteristics of a real situation, butreports of an incident without scientific intervention.The results showed that there is still no maximum performance PKScadres DPC Tassel in winning the parliamentary elections in 2014, it can beknown from less than the maximum deployment of cadres to many existing areasdikecamatan Tassel, the PKS cadres is ditngkat national things result concernedthe motivation to drop the cadres and affect the image of the PKS was also loweramong people with only a few frames be incentives.Keywords: PKS, Performance, Organizational